The Influence of Gymnastics on Disminore Inadolescent Women - Priharyanti Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2023)
Dysmenorrhea is a condition that occurs when menstruation can interfere with activity and require treatment. Handling of dysmenorrhea is divided into two pharmacologically can be handled with analgesic therapy while non-pharmacologically can be treated with relaxation techniques such as gymnastics. Gymnastics is one of the non-pharmacological methods to reduce dysminorea. Method Quasi experimental research design with one group pre-test - post test design without control group. The number of samples 33 people. Data collection using observation sheets by examining the scale of dysmenorrhea before and after given the exercise intervention. Results In this study using the Wilcoxon signed rank analysis method. . Z value = -4.893 and p value 0.000 ≤ 0.05 Ho is rejected Ha is accepted, which means that there is an effect of gymnastics on decreasing the disminore pain scale between before Gymnastics and after Gymnastics.